Sobredentaduras mandibulares inmediatas: revisión de literatura - Ribeiro, Adriana Barbosa [UNESP]; Pita, Murillo Sucena [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Falcón-Antenucci, Rosse M. [UNESP] (Universidad Central de Venezuela, 2012)
Conventional complete denture even though well confectioned, could present deficiencies in the retention, stability and support, in addition uncomfortable and retention of food below it. The overdentures have been considered an alternative to resolve problems and negative experiences with the conventional dentures, thus also can be an alternative to the complex treatments (surgical/prosthetic) with implant-supported prosthesis. In the attempt to reduce the healing time for the confection of the dentures showed higher rates of success to the implants when immediate mandibular overdentures were used in the rehabilitation of edentulous patients. The aim of this paper was to discuss by means of a Literature review, the viability of the use of mandibular implant-supported overdentures. The immediate mandibular overdentures have been showed like a reproducible method, predictable and confidence to provide an efficient function to the total edentulous patients.

Las Prótesis totales convencionales aún cuando bien confeccionadas, pueden presentar deficiencias en la retención, estabilidad y soporte, además de la incomodidad y acumulo de alimentos. Las sobredentaduras sobre implantes fueron consideradas una alternativa para solucionar problemas y experiencias negativas con las prótesis convencionales, así también pueden ser una alternativa a los tratamientos complejos (quirúrgico/protésico) con prótesis fijas soportadas por implantes. Buscando reducir el período de cicatrización para la confección de las prótesis, las investigaciones mostraron altos índices de éxito para los tratamientos con sobredentaduras mandibulares inmediatas sobre implantes, que fueron utilizadas en la rehabilitación de pacientes edéntulos. Este trabajo tiene como objetivo abordar, por medio de una revisión de literatura, la viabilidad de la utilización de sobredentaduras mandibulares implanto retenidas. Los implantes de carga inmediata que retienen una sobredentadura mandibular que ha mostrado ser un método reproducible, previsible y de confianza para restablecer una eficiente función masticatoria a los pacientes totalmente edéntulos.
Immediate mandibular overdentures: review of literature
Keywords: Overdentures; Immediate loading; Dental implant; Sobredentaduras; Carga imediata; Implantes osseointegrados